The Role of Frictions due to Top Management in Alliance Termination Decisions: Insights from Established Bio‐Pharmaceutical Firms. (24th November 2021) - Ghosh, Anindya; Klueter, Thomas
Abstract: This study examines the termination of research alliances by established firms accessing knowledge from smaller research partners. We relax the assumption implicit in the internal tension perspective of alliance termination that signals from a partner are readily processed and acted upon. Instead, we consider that large firms involved in the alliance may have distributed decision‐making structures involving both alliance managers in charge of day‐to‐day activities and top managers who are responsible for a company's strategic decision making. Using the information‐processing view of the firm we theorize on frictions as top managers evaluate the balance of tensions within the alliance. First, signals collected by units involved in the alliance must receive top management attention. Second, the accuracy and reliability with which signals are evaluated and acted upon is contingent on the composition of the top management team. An analysis of 235 alliances initiated by Top 50 pharmaceutical firms broadly supports our theoretical framework.